2020
DOI: 10.1007/s10340-020-01255-1
|View full text |Cite
|
Sign up to set email alerts
|

Brightness mediates oviposition in crepuscular moth, Grapholita molesta

Abstract: Plant colouration is known to be used by some nocturnal flower-visiting insects to foraging among colourful flowers in dim light. However, it remains unknown whether crepuscular species possibly reliably discriminate plant colouration (i.e. colour and/or brightness) for oviposition even driven by challenges of variably light conditions and similar leaf colouration. Here, we explored this question in the oriental fruit moth Grapholita molesta, a major pest of stone fruits worldwide, using coloured squares under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…For several species-groups, however, it is still unknown which type of photoreceptor is most important for achromatic signal detection (Table 1). Presumably, the use of achromatic cues also plays a role in detecting oviposition sites for herbivorous insects (Prokopy et al, 1975;Blake et al, 2020;Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For several species-groups, however, it is still unknown which type of photoreceptor is most important for achromatic signal detection (Table 1). Presumably, the use of achromatic cues also plays a role in detecting oviposition sites for herbivorous insects (Prokopy et al, 1975;Blake et al, 2020;Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As such, gravid females can discriminate volatiles emitted from host plants from those of non‐host plants, from those of different host plant species, and even from plants of different developmental stages (Piñero & Dorn, 2009; Najar‐Rodriguez et al, 2013). When a female moth senses a plant species, the similar volatile chemicals released between sunny and shaded sites become less distinguishable, so visual rather than olfactory cues are believed to be more important in short‐range preference determination (Yang et al, 2020). In this study, G. molesta significantly preferred to lay eggs in the light even when exposed to dark conditions with attractive odor stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…However, vision may be crucial for G. molesta females to discriminate potential oviposition sites within a plant species. A recent study has demonstrated that G. molesta can modify their oviposition behavior in response to brightness in dim light (Yang et al, 2020). However, whether or not the preference for sunny sites can be guided by light in dim or variable light conditions is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…One face of the apparatus was illuminated with white LED light (9 W, c. 500 lux) and the other five sides were left in darkness (Figure S1C). The spectrum of the LED light ranged from 400 to 700 nm (Yang et al, 2020). Experimental larvae (n = 3 replicates of 30 larvae each) were held in darkness for 30 min prior to testing and then placed in the central arena of the apparatus.…”
Section: Assay Of Horizontal Phototaxismentioning
confidence: 99%